Penerapan Model Think Talk Write Berbantuan Media Gambar Seri Untuk Meningkatkan Aktivitas dan Kemampuan Menulis Karangan Narasi Siswa SD - Zulia Apriyana; Johanes Sapri; Hasnawati (Universitas Bengkulu, 2023)
This Study aims to determine the application of the Think Talk write model using the media series on the writing material narrative essay in CLASS VI B SDN 17 Bengkulu in Indonesian subjects. This research aims to increase activities and capabilities with the implementation of the Think Talk Write model using the Media series image in class VI B SDN 17 Bengkulu. This research is class action research. The research subject is teacher and student of class VI B SDN 17 Bengkulu City. Research instruments in the form of observation sheets and test sheets. The test data analysis technique uses the average formula value and percentage of the classical learning submission. Observation Data is analyzed using average formula score, highest score, lowest score, score difference and value range for each criterion. Results of the average teacher activity cycle I acquired 32.25 Cycles II acquired 40.25. The student activity of cycle I got an average of 34.75 and cycle II gained 40.75, while for the ability to compose a narrative of students at cycle I with an average of 74.6 and a classical learning submission of 60%. and cycle II with an average of 80.55 with a classical study of the classic, 90%. Thus, it can be concluded that the application of Model learning Think Talk Write using the Media Image series can increase the activity and ability of writing narrative essay in class VI B SDN 17 Bengkulu City